2004
DOI: 10.1021/jp047410k
|View full text |Cite
|
Sign up to set email alerts
|

A Vibrational Spectroscopic Study of the Fate of Oxygen-Containing Functional Groups and Trapped CO2 in Single-Walled Carbon Nanotubes During Thermal Treatment

Abstract: The oxygen-containing functional groups, introduced by common purification procedures, on single-walled carbon nanotubes (SWNTs) made by both the HiPco and laser-ablation (Rice Tubes) techniques are studied by Fourier Transform Infrared (FTIR) spectroscopy from 90 to 1400 K under vacuum. The fate of the functional groups under heating and the physically trapped CO2 generated from the decomposition of these functional groups are investigated. Vacuum heating to ∼1300 K removes most of the oxygen-containing funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 29 publications
(77 reference statements)
8
63
0
Order By: Relevance
“…Some of the other features in Figure 1 have been discussed elsewhere. 13,40,41 The broad band at ∼3450 cm -1 indicates the loss of H-bonded sOH groups and/or physisorbed H 2 O. The structure in the 1680-1735 cm -1 range has been assigned to the loss of various carbonyl (>CdO) species.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the other features in Figure 1 have been discussed elsewhere. 13,40,41 The broad band at ∼3450 cm -1 indicates the loss of H-bonded sOH groups and/or physisorbed H 2 O. The structure in the 1680-1735 cm -1 range has been assigned to the loss of various carbonyl (>CdO) species.…”
Section: Resultsmentioning
confidence: 99%
“…11). [25] We have also recently shown that NH 3 adsorption appears to be functionality/defect mediated and that pristine single-walled CNTs show no sign of adsorption of ammonia (Fig. 12).…”
Section: Self-assembled Monolayer Compatible With Metal Surface Acousmentioning
confidence: 77%
“…11 IR peak evolution of nitric acid treated HiPco samples during vacuum heating from 300K to 1300K. [25] Fig. 12 IR of Ammonia adsorption at 94K on nanotubes treated to successively higher temperatures, a process that drives off surface functionality and heals defects.…”
Section: Self-assembled Monolayer Compatible With Metal Surface Acousmentioning
confidence: 99%
“…However, it is not inaccurate to assume that some degree of removal of surface functionalities and oxygenated defects along the nanotube sidewalls occurred as a result of the thermal treatment. In fact, it has been reported that heating (up to 1400 K) can readily defunctionalize (i.e., deoxygenate) HiPco tubes [14]. The E 1u mode of carbon nanotubes, due to C=C double bonds, at around 1581 cm −1 can be seen in both spectra, whose posi- tion is relatively unaffected by the localized addition and removal of oxygenated groups; however, its intensity changes slightly upon more severe oxidation.…”
Section: Mid-irmentioning
confidence: 93%
“…HCl treatments, especially in the presence of moist air, are known to reduce metal impurities in tubes without necessarily introducing defects in the intrinsic sp 2 carbon framework [14]. Samples of ozone and ozone/H 2 O 2 -treated carbon nanotubes were subsequently placed in ceramic crucibles, and heated in a quartz tube at 700 • C for 2 h (a ramp rate of 10 • C/min) in a continuous flow of argon to prevent sample destruction, prior to cooling to room temperature.…”
Section: Heat-treated O 3 -Functionalized Swcntsmentioning
confidence: 99%